Studies on Isolation of Salmonella from Sea Foods 1. Comparison of Enrichment and Selective Media for Recovery of Salmonella from Fish - James, M. Arul; Iyer, K. M. (Fishery Technology, 1972)
Three enrichment broths and six plating media were compared for efficiency of detection Salmonella in the presence of numbers of Coliforms (105 /ml) and proteus (103 /ml) from artificially inoculated fish samples. Recovery experiments with Salmonella anatum, S. typhimuriwn and S. enteritidis indicated that the two enrichment broths viz. Dulcitol Selinite (DSE) and Selinite Cystine (SC) were equally efficient. Further, the viability of Salmonella, inoculated into fish muscle and kept at 4 °C for 48 hours, was found to be not affected by the low temperature storage. Selective plating media like Xylose Lysine Deoxycholate agar (XLD), Brilliant Green Sulphadiazine agar (BGS) and Brilliant Green agar (BG) were found to be superior in performance to Salmonella Shigella agar: (SS) and Bismuth Sulphite agar (BiS).